Greening the esterification between isosorbide and acetic acid - Inayat, Alexandra; van Assche, Alexander; Clark, James H.; Farmer, Thomas J. (Sustainable Chemistry and Pharmacy, 2018)
This contribution deals with the investigation of greener conditions for the preparation of 2,5-diacetyl-isosorbide from the bio-based substances isosorbide and acetic acid. The influence of solvent, catalyst and reactant ratio on the course of the isosorbide conversion and selectivity to 2,5-diacetyl-isosorbide as well as to the intermediate 2-acetyl-isosorbide is examined. It was found that the conventionally used solvent toluene can be substituted by the greener solvent n-propyl acetate. Additionally, the homogeneous acid catalyst p-toluene sulfonic acid can be replaced by the heterogeneous catalyst Amberlyst-15, resulting in an easier isolation of the desired 2,5-diacetyl-isosorbide, this being an important precursor for the vasodilatory drug isosorbide-5-nitrat